The Utilizing Systematic Literature Review And Bibliometric: Study In Environment, Social And Governance For Corporate Finance Performance - Muhammad Dandy Resafahlevi Nasution; Sulaeman Rahman Nidar; Erman Sumirat (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
The goal of this study was to provide a comprehensive review of recent works published in highly regarded journals while using bibliometric analysis and mapping to examine academic literature pertaining to ESG. A combination of bibliometric and systematic literature review techniques were used in this study. A well-defined search string was used to retrieve data from the Scopus database, and 256 documents were analysed using bibliometric techniques. Biblioshiny was used for performance analysis, and VOSviewer was used for science mapping. Seventy chosen articles were subjected to a thorough review following additional refinement. Stakeholder, legitimacy, and signalling theories are the fundamental frameworks that connect ESG to financial performance, according to the study's findings. Because of their lower risk profile, socially conscious businesses typically have lower capital costs. By grouping research into four major clusters, such as "CSR/ESG determinants and firm performance" and "Investors' perception," the study also describes the knowledge structure”. This study provided a current synthesis of recent research in the field by analyzing the literature using both qualitative (systematic review) and quantitative (bibliometric) methods.